Estudo da relação da Demonstração do Fluxo de Caixa (DFC) com o estágio do ciclo de vida das organizações nas instituições de ensino com capital aberto listadas na BM&F/Bovespa - Gonçalves, Aguinaldo Aparecido (2013)
This work aims to study the relationship between Statement of Cash Flows (SCF) and the life cycle of organizations chart in Educational Institutions listed publicly traded on the BM & FBovespa. Initially we seek to demonstrate the importance of these institutions in the economy and their representation in the teaching of Brazil, since although they are few who participate in this market are extremely significant, given its scope and number of students. Furthermore, the authors discuss briefly the history of the entry of such institutions in the Brazilian market. Then many of Organizational Life Cycle in the literature are presented. The study shows that, although they are named differently, they all, in essence, show that the evolutionary process models have similar characteristics, however, emphasis was placed on models that emphasize the use of SCF in setting the stage lifecycle. In this sense, the work was to support the work of research Borinelli (1998), who studied the relationship lifecycle of small businesses through its financial statements, but have not used the SCF in their analysis, dealing with companies not required of preparation and publication. The study used quantitative research methodology of secondary data. Statements of Cash Flow, the financial statements and management reports of the institutions of education participating in this research, focusing mainly on the SCF were surveyed. The results demonstrated that it was possible to establish a relationship through the use of SCF in determining the stage of the life cycle